Stay - Caletti, Deb (Simon Pulse, 2011)
Clara and her father travel to a remote region of Washington State when she notices that her boyfriend, Christian, is developing obsessive behaviors, and after arriving, Clara meets two brothers who captain a sailboat, a lighthouse keeper who is hiding something, and a friend of her father who knows the lighthouse keeper's secret.